Primary Splenic Leiomyosarcoma in a Dog - de Vargas Ritter, Larissa Eugênia; Pereira, Jaíne; Irgang, Andressa; Malvestio, Lygia Maria; Jacob Kolling, Giovani (Acta Scientiae Veterinariae, 2024)
Background: Leiomyosarcoma is a malignant mesenchymal neoplasm that commonly occurs in the uterus and gastrointestinal tract. Its primary occurrence in the spleen is considered rare, corresponding to only 4% of cases. The diagnosis must be made based on the patient’s medical history, clinical signs and complementary exams. The gold standard test for a definitive diagnosis is immunohistochemistry. This paper reports a case of one dog suffering from primary splenic leiomyosarcoma, emphasizing the importance of the immunohistochemical exam to conclude the diagnosis and select an ideal treatment. Case: A 10-year-old male Labrador dog, was treated after presenting for 4 days with hyporexia, constipation and sporadic cases of emesis. A physical examination of the patient revealed a body condition score of 9, with 1 being extremely thin and 9 being obese, abdominal pain during palpation, 5% dehydration, apathy and a slightly distended abdomen. Radiographic and ultrasound exams were requested to evaluate the thoracic and abdominal organs. In view of the results, the patient was referred to hospital for hydration, followed by a median celiotomy and orchiectomy. Blood count and serum biochemistry were requested as preoperative exams. In a laboratory evaluation, the animal’s blood count revealed normochromic normocytic anemia, thrombocytosis, high levels of total plasma protein and neutrophilia. The patient’s serum biochemistry profile indicated an increase in the enzyme activity of aminotransferase (AST), alkaline phosphatase (AP) and urea. An ultrasound exam revealed a 7.03 x 7.86 cm coarse-textured mass in the spleen. Right lateral view chest X-rays showed diaphragmatic compression by a round radiopaque structure projecting cranially, surpassing the 7th intercostal space, while the thoracic ventral-dorsal projection revealed absence of radiographic findings suggestive of pulmonary nodules or masses. The histopathological examination performed after total removal of the mass revealed moderately differentiated myofibroblastic sarcoma. However, an immunohistochemical test to confirm the diagnosis revealed immunoreactivity to vimentin (V9) and smooth muscle actin (1A4), conclusive for leiomyosarcoma. Discussion: Leiomyosarcoma typically develops silently, without displaying clinical signs or presenting nonspecific clinical signs, depending on its location. Patients with stromal tumors may present with anorexia, vomiting, polydipsia, lethargy, weakness, weight loss, enlarged abdomen and abdominal pain, which partially coincides with this case. In addition, enlarged spleen size may lead to displacement of adjacent viscera, causing signs of abdominal pain, vomiting and constipation, which coincide with the case in question. Leiomyosarcoma can be diagnosed based on the patient’s medical history, physical examination and complementary tests, particularly immunohistochemistry, which proved to be of paramount importance for the definitive diagnosis of this patient. Changes in laboratory test results are a consequence of the neoplasm, its localization, and the patient’s clinical status. In cases of neoplasia, surgical resection is a long-standing procedure that is efficacious in halting tumor growth. Moreover, the proposal of total splenectomy is based on the level of impairment of the organ by the mass. Given the difficulty in assessing its histogenesis, immunohistochemistry testing proved to be necessary to confirm the diagnosis, showing neoplastic cells immunoreactive to vimentin and actin, and positive for cell proliferation antigen, enabling the diagnosis of leiomyosarcoma. Keywords: immunohistochemistry, smooth muscle, spleen, splenic neoplasm, stromal tumors. Título: Leiomiossarcoma esplênico primário em cão Descritores: baço, imuno-histoquímica, músculo liso, neoplasia esplênica, tumores estromais.